(untitled) (Abhat Journal, 2023)
The Libyan legislature did not expressly stipulate the permissibility of inspection in electronic media and the acceptance of digital evidence extracted from it ,however, according to the Libyan code of criminal procedure ,it can be accepted because it is useful in revealing the truth similar to physical evidence ,bearing in mind that the search is carried out in accordance with the controls stipulated by the legislator when searching for physical evidence ,the most prominent of which -in the search of places-is obtaining permission ,and if the inspector encounters ,upon inspection ,a problem of entanglement of the devices, then the matter differs according to whether the devices are within the scope of the state ,and if it is outside the scope of the state ,then the matter is governed by international agreements ,as for the personal search ,what usually happens in the search of mobile phones in the possession of person ,they often contain secrets and messages related to the accused and others ,which is considered a violation of sanctity of private life and the confidentiality of correspondence that the legislator was keen to ensure their protection in various laws ,which requires the intervention of the legislator to surround them with sufficient guarantees when searching personally ,provisions for the inspection of regular mail ,if the inspection is carried out by the service provider ,the matter requires obtaining permission from the partial judge ,this is what the legislator also requires when intercepting correspondence ,bearing in mind that the search warrant is limited to correspondence between those involved ,whenever possible